COMPARISON OF RAPID IMMUNOCHROMATOGRAPHIC ASSAYS (ICT MALARIA P.F. /P.V. TEST AND OPTIMAL TEST) WITH MICROSCOPY FOR DETECTION OF MALARIA PARASITES - MUKTIKESH DASH (International Journal of Pharma and Bio Sciences, 2013)
This study was conducted to compare the ability of developed immunochromatographic assays, ICT malaria P.f./P.v. test and OptiMAL test with standard microscopy for the diagnosis of malaria parasites. Blood samples were obtained from 150 patients clinically suspected of having malaria. A total of 59 samples (39.3%) were positive by blood films while 64 (42.7%) were positive by ICT p.f./p.v. and 52 (34.7%) by OptiMAL tests. The blood film indicated that 32.2% (19 of 59) of patients were positive for P. vivax and 67.8% (40 of 59) were infected with P. falciparum. ICT P.f./P.v. test showed 23.4% (15 of 64) were positive for P. vivax and 76.6% (49 of 64) were infected with P. falciparum. Similarly, OptiMAL test detected 30.8% (16 of 52) were positive for P. vivax and 69.2% (36 of 52) were infected with P. falciparum. ICT P.f./P.v. test had sensitivities 78.9%, 87.5% and specificities 100%, 87.3% for P. vivax and P. falciparum respectively. OptiMAL test showed sensitivities 84.2%, 80% and specificities 100%, 96.4% for P. vivax and P. falciparum respectively. Thus these rapid immunoassays (ICT P.f./P.v. and OptiMAL) tests can be used as supplementary test to traditional light microscopy for the diagnosis of malarial parasites.